PENGARUH PELATIHAN DAN BUDAYA ORGANISASI TERHADAP PERILAKU KERJA KARYAWAN PADA PT. DIMENSI BARUMAS PERDANA DI PEKANBARU - Bareckman '; Marzolina '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research held in PT. Dimensi Barumas Perdana Pekanbaru. This research held in order to analyze the influence of training and organization culture to employees’ work behaviour. Population are all employees, consist of 69 people. Considering the number limitation so sampling method used is census that covers all employee as the respondents.Variables used are training and organization culture as independent dan employees’ work behaviour as dependent. Data analyzed by using descriptive analysis and multiple regression analysis by using SPSS 19 for windows. Result of this study shows that simultenously both organization culture and leadership significantly influence employees’ work behaviour. However, partially, only training gives significant effect to employees’ work behavior, while organization culture though positively but gives no significant effect to employees’ work behavior. Employee’s work behavior is quite effected by the effectivity of training and the implementation of organization culture as up to thirty six percent of employees’ work behavior is determined by the variation of training and organization culture. It is recommended to company to conduct training pre-analysis before setting the training agenda up, socializing organization culture values in every daily briefing and implementing a reward and punishment program that may encourage more positive work behavior.Keywords: Training, Organization Culture and Work Behavior